PERLINDUNGAN HUKUM TERHADAP DEBITUR ATAS EKSEKUSI OBJEK JAMINAN FIDUSIA OLEH PERUSAHAAN PEMBIAYAAN DI PT. SINAR MAS MULTIFINANCE - ENNI MARTALENA PASARIBU (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Sunarmi2. T. Keizerina Devi A3. Dedi Harianto Financing company is a business which operates in a non-bank financial institution by providing fund or capital by not taking the fund directly from the people in the from demand deposit, deposit, savings, and P.G (promissory note). The result of the research showed that debtor’s default in fiduciary contract between debtor and financing company is that debtor does not fulfill one of the clauses in the contract. He does not keep and take care of the collateral, motor cycle/mobile, from being broken or missing. Legal protection on the execution of the fiduciary collateral by financing company is as follows, debtor has the right to file compensation, execution should be attended by the police, execution should be based on court’s verdict, selling fiduciary collateral is throught public auction, and dispute between debtor and creditor has to be trought litigation in District Court and BPSK (Costumer Dispute Settlement Board).Keywords: Legal Protection, Debtor, Execution of Collateral